Pengaruh Kompetensi dan Self Efficacy Terhadap Kinerja Takmir Masjid (Study Kasus Takmir Masjid Kec, Pakong) - Maisaroh, Sitti; Ismail, Iriani (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The aims of this study are to determine the effect of competency and self-efficacy on the mosques administrators performance in Pakong, Pamekasan Regency, partially and simultaneously.This analyzes includes the independent variables are competence and self-efficacy variables, and the dependent variable is the mosques administrators performance. It used the Likert scale to measure the indicators of each variable. It has 870 people or employees as population, while the number of samples used in this study were 90 mosques administrators. It used the f test to determine the effect of Competence and Self Efficacy on mosques administrators performance simultaneously, while used the t test to determine the effect of Competence and Self Efficacy on mosques administrators performance partially.So the research type is quantitative research. Using the multiple linear regression analysis, the results showed that the competency has a positive effect on the mosques administrators performance partially with a positive beta value of 0.695 and a significant value is 0.000 and the tcount is 6.067 1.98761. Self-Efficacy also has a positive and significant effect on the mosques administrators performance partially with a positive beta value is 0.527, and a significant value is 0.000 and a tcount is 3.601 1.98761. Then, it is known that the independent variables (Competency and Self Efficacy) have a significant effect on the dependent variable (mosques administrators performance) simultaneously with a positive beta value is 0.619 or 61.9%, and a sign value is 0.000 0.05. Keywords: Competence, Self Efficacy, Mosques Administrators (Takmir) Performance